A Comparative Study of the Objectives, Teaching Methods, Educational Content, and Assessment Strategies in Environmental Education within the Curricula of Selected Countries - Ashrafi , Maryam; Barghi, Isa; Maleki Avarsin, Sadegh; Yarigholi , Behbood (Assessment and Practice in Educational Sciences, 2025)
This study aims to compare the goals, teaching methods, content, and assessment strategies of environmental education in the national curricula of Iran, the United States, Canada, and Finland to identify similarities, differences, and opportunities for improvement. The study employed a qualitative, comparative-descriptive design using George Bereday’s four-stage model (description, interpretation, juxtaposition, and comparison). National curriculum documents, educational policy papers, research articles, and official reports from the four selected countries were purposefully sampled and analyzed. Data collection focused on primary and secondary education systems, with particular attention to environmental education content, objectives, pedagogical approaches, and evaluation methods. Credibility of the sources was ensured through internal and external validation, and data were analyzed using thematic comparison and content synthesis. All countries share a strong emphasis on fostering environmental responsibility, resource conservation, and cognitive understanding of environmental systems. The U.S., Canada, and Finland apply integrated goals encompassing knowledge, attitudes, and skills, while Iran lacks a clear emphasis on skill development. Teaching strategies across all countries prioritize active and experiential learning, though methods such as simulation, digital media, and lab-based inquiry are more prevalent in Western systems. Content related to ecology, sustainability, and environmental threats is uniformly present, with only minor terminological differences. Assessment practices vary: Finland favors qualitative feedback, the U.S. emphasizes standardized testing, and Canada and Iran apply performance-based and innovative evaluative methods. While there is global consensus on the core components of environmental education, national approaches vary according to cultural, structural, and technological contexts. The study highlights the need for Iran to integrate more practical skill-building, modernize assessment tools, and adopt a more interdisciplinary and student-centered approach. Comparative insights from leading systems offer valuable guidance for improving environmental education within Iran and similar contexts.